2000
DOI: 10.1016/s0006-3495(00)76603-3
|View full text |Cite
|
Sign up to set email alerts
|

Fast Events in Protein Folding: Structural Volume Changes Accompanying the Early Events in the N→I Transition of Apomyoglobin Induced by Ultrafast pH Jump

Abstract: Ultrafast, laser-induced pH jump with time-resolved photoacoustic detection has been used to investigate the early protonation steps leading to the formation of the compact acid intermediate (I) of apomyoglobin (ApoMb). When ApoMb is in its native state (N) at pH 7.0, rapid acidification induced by a laser pulse leads to two parallel protonation processes. One reaction can be attributed to the binding of protons to the imidazole rings of His24 and His119. Reaction with imidazole leads to an unusually large con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 52 publications
2
76
0
Order By: Relevance
“…Investigation of the pressure induced formation of an I form, similar to the one observed at low pH and in the kinetic folding pathway, has revealed that the volume of this species is considerably smaller (∆V ) -70 mL/mol) compared to that of the N form (12). Recent time-resolved photoacoustic measurements using a nanosecond pH jump as the trigger for the unfolding reaction N f I showed that this huge contraction is produced within a few microseconds (13). This finding suggests that much of the structural change for the N f I transition, triggered by protonation of His24 and His119, occurs on the same time scale.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Investigation of the pressure induced formation of an I form, similar to the one observed at low pH and in the kinetic folding pathway, has revealed that the volume of this species is considerably smaller (∆V ) -70 mL/mol) compared to that of the N form (12). Recent time-resolved photoacoustic measurements using a nanosecond pH jump as the trigger for the unfolding reaction N f I showed that this huge contraction is produced within a few microseconds (13). This finding suggests that much of the structural change for the N f I transition, triggered by protonation of His24 and His119, occurs on the same time scale.…”
mentioning
confidence: 79%
“…Thus, the structural changes sensed by NR are complete within a few milliseconds. The few pH-jump experiments performed on ApoMb with submillisecond resolution monitored only volume changes accompanying the unfolding reaction N f I, suggesting that most of the large volume change accompanying the formation of the I state (12) is produced within a few microseconds (13), with very little, if any, additional volume changes on the millisecond time scale (14). The pH dependence of the amplitude of the fast component ( Figure 6) and its lifetime (2.7 µs) both suggest that this transient directly senses the early events of the N f I transition, whereas the slower component may reflect a subsequent rearrangement of NR, possibly, to the final location inside the new conformation of the protein.…”
Section: Steady-state Fluorescence Emission Nr In Water Ismentioning
confidence: 99%
“…Although photoacoustic calorimetry has been widely used to study photoinitiated nonradiative process in solution, the application of this method to protein folding is quite new (30,33). The schematic of a photoacoustic calorimetry apparatus is shown in Fig.…”
Section: Refolding Kinetics Of the Peptides By Photoacoustic Calorimementioning
confidence: 99%
“…This mutation not only alters the strand register but also decreases the overall structural stability of the mutant peptide. Here, the peptide with the S-D P-G-K turn and the peptide with the T-S-D-G-K turn are cyclized with the aid of our photolabile linker, and we have studied the manner in which these two turn sequences influence the kinetics of recovery of the hairpin structure by photoacoustic calorimetry (32,33) (Fig. 2).…”
mentioning
confidence: 99%
“…Using 2-nitrobenzaldehyde as an irreversible caged proton, we have induced a rapid proton concentration jump in solution and measured the reaction volume and the rate constant for the formation of water from protons and hydroxyls [20][21][22]. The same experimental methodology has also been used to induce proton transfer reactions in more complex systems, including model polypeptides [23,24] and proteins [25]. The method has proved useful also for the determination of the pK a of the acinitro intermediate in the photochemical reactions of 2-nitrobenzyl compounds [21].…”
Section: Introductionmentioning
confidence: 99%